Road Quality Assessment Using International Roughness Index Method and Accelerometer on Android - Setiawan, Eko Budi; Nurdin, Hadi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 10, No. 2 August 2019DO - 10.24843/LKJITI.2019.v10.i02.p01, 2019)
The quality of road conditions can determine comfort in driving. To find out the condition of a road whether it has good surface quality, it can use an accelerometer sensor contained in an android smartphone. This research uses the International Roughness Index (IRI) method combined with the accelerometer sensor and the Global Positioning System (GPS). Application of the results of this study can be used to facilitate the contractor maker and road repair, so they can find out which points need to be repaired. Testing is done using two different vehicles, car and motorcycle. Smartphones with road quality detection applications are attached to the car and motorcycle vehicles using a phone holder. This is to record vibration that occurs while the vehicle is moving based on road conditions. The vibration recording results are then validated in a visual observation to determine the accuracy of the assessment results. Based on the test results the level of accuracy on the car is 90% and the motorcycle is 30%.